2011
DOI: 10.1007/s00430-011-0188-z
|View full text |Cite
|
Sign up to set email alerts
|

A DNA vaccine expressing CFP21 and MPT64 fusion protein enhances BCG-induced protective immunity against Mycobacterium tuberculosis infection in mice

Abstract: The efficacy of Bacillus Calmette-Guérin (BCG) vaccine in preventing adult tuberculosis (TB) is highly variable. Genetic differences between BCG vaccine substrains, which can be divided into early strains and late strains based on the loss of region of difference two (RD2), may result in the variability and BCG substrains. The effect of lack of RD2 on the protective efficacy of BCG substrains against TB remains unknown. In this study, we demonstrated that CFP21 and MPT64(rCM) fusion protein, encoded by RD2 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The detail procedures were performed as previously described [35]. Tested cDNAs were normalized to the endogenous RNA levels of GAPDH.…”
Section: Expression Of Cytokines In Lung Detected By Realtime Pcrmentioning
confidence: 99%
“…The detail procedures were performed as previously described [35]. Tested cDNAs were normalized to the endogenous RNA levels of GAPDH.…”
Section: Expression Of Cytokines In Lung Detected By Realtime Pcrmentioning
confidence: 99%
“…These studies revealed that BCG prime-boost approach could activate T cell to evoke strong immune responses including both CD4+ T cell and CD8+ T cell immune responses [10]. We thus focused on the prime-boost strategy that combines BCG with a subsequent booster vaccine candidate.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that Ag85A and Ag85B stimulate strong humoral and cell-mediated immune responses and produce significant protection against Mycobacterium tuberculosis H37Rv challenge (18,20,22,38). In addition, MPT64, a member of the culture filtrate protein (CFP) family, can induce a strong T cell response (42). TB10.4, a member of a subfamily of the ESAT6 family, is even more vigorously recognized than ESAT-6 (6-kDa early secreted antigen target of M. tuberculosis) in TB patients (35).…”
Section: Discussionmentioning
confidence: 99%